COMPUTATIONAL STUDY OF AERO-SPIKE ON BLUNT BODY. (October 2019) - Edwin, M.; Isaac, Sujay Iswarian; Pradeep, M.; Nagarajan, L.
Abstract: An Aero-Spike involved to the stagnation point of a Semi-circular Blunt frame modifications its movement field and reduces the sweptback graft. The blunt body with aero-spike with different L/D relations (1, 2) and aero-spike shapes of truncated hemisphere, extended hemisphere, Simple spike and flat faced cone at Mach number 2 and at different angles of attack (0, 5, 10. 15) were computationally analysed using ANSYS Fluent. A recirculation zone forms in front of the blunt body and its gives more streamlined shape to the blunt body. Larger recirculation zone reduces the coefficient of drag efficiently, thus increasing length of the spike results in increase of recirculation sector and reduction in drag. By increasing angles of attack the coefficient of drag also increased. At 0 deg position of spell single disk with L/D ratio of 2 reduces the co efficient of drag efficiently.